Dental decay and associated factors in Iranian three-year-old children - Ghazizadeh Ahsaie, Mitra; Deghatipour, Marzieh; Shahzadeh Fazeli, Kazem; Bastani, Parvin; Ehdaivand, Farnaz; Ghorbani, Zahra (Journal of Dental School, 2019)
Objectives The aim of this study was to assess dental caries and associated factors in children aged three years living in Varamin, Iran. Methods Eight hundred and fifteen three-year-old children were recalled randomly through the records existing in healthcare centers of Varamin, Iran. Two hundred and three mothers were also examined to assess the relationship between the oral health of mothers and children. Dental examinations were performed by two calibrated senior dental students using decayed missed filled teeth (dmft/DMFT) indices according to the WHO oral health survey basic methods. Demographic and oral-health care behavior data were collected using a standard questionnaire. Results The mean DMFT was 2.69 ± 3.492 years (range 0–19 years). No significant difference was seen in dental care behavior of males and females; 43.4% of children were caries-free. A positive correlation was detected between mother’s DMFT and child’s dmft (r = 0.27, P < 0.0001). Adjusted regression analysis showed that dental caries was observed more frequently in children having mothers with DMFT> 12 compared to mothers with DMFT less than 6 (CR: 1.55; 95% CI: 1.02–2.35) after controlling for child’s sex and behaviors. Conclusion This study showed that more than half of the three-year-old children experience dental caries and there is a positive correlation between the DMFT of mothers and dmft of their children.